2018
DOI: 10.1097/gme.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and its components in premenopausal and postmenopausal women: a comprehensive systematic review and meta-analysis on observational studies

Abstract: The prevalence of MetS is relatively high in postmenopausal women and was more prevalent among postmenopausal than premenopausal women. Menopausal hormone therapy should be used with caution in patients with MetS, as its safety has not yet been evaluated among MetS patients and meticulous evaluation of each individual patient before starting MHT is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 36 publications
2
42
2
1
Order By: Relevance
“…Women's cardiometabolic risk significantly increases after shifting into menopause [3], and CVD is generally the leading cause of mortality in post-menopausal women [4]. A recent meta-analysis showed that post-menopausal women had about 1.5~4 times higher cardiometabolic risk and 3.5 times higher risk of development of metabolic syndrome (MetS) than premenopausal women [5]. Cardiometabolic risk is particularly prevalent in patients diagnosed as having MetS, and it is not only associated with aging but also, at least in part, related to decreased levels of ovarian hormones during the menopausal transition and beyond [3].…”
Section: Introductionmentioning
confidence: 99%
“…Women's cardiometabolic risk significantly increases after shifting into menopause [3], and CVD is generally the leading cause of mortality in post-menopausal women [4]. A recent meta-analysis showed that post-menopausal women had about 1.5~4 times higher cardiometabolic risk and 3.5 times higher risk of development of metabolic syndrome (MetS) than premenopausal women [5]. Cardiometabolic risk is particularly prevalent in patients diagnosed as having MetS, and it is not only associated with aging but also, at least in part, related to decreased levels of ovarian hormones during the menopausal transition and beyond [3].…”
Section: Introductionmentioning
confidence: 99%
“…With age, a decrease in lean body mass, a decrease in skeletal muscle mass, an increase in the percentage of adipose tissue, as well as a decrease in basal metabolism and total energy expenditure are observed [ 83 ]. Three independent meta-analyses demonstrated that the incidence of MetS in post-menopausal women is relatively high and considerably higher than in pre-menopausal women [ 84 , 85 , 86 ]. In addition, a higher probability of diagnosing MetS in post-menopausal women than in their pre-menopausal counterparts has been demonstrated, based on the assessment of MetS components, regardless of the type of MetS diagnostic criteria [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three independent meta-analyses demonstrated that the incidence of MetS in post-menopausal women is relatively high and considerably higher than in pre-menopausal women [ 84 , 85 , 86 ]. In addition, a higher probability of diagnosing MetS in post-menopausal women than in their pre-menopausal counterparts has been demonstrated, based on the assessment of MetS components, regardless of the type of MetS diagnostic criteria [ 85 ]. It is suspected that MetS may also be associated with post-menopausal hyperandrogenism in women.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, LAP and VAI were also found to be effective markers for identifying the metabolically obese, normal-weight individuals who are predisposed to diabetes and CVD development (12) . In a recent meta-analysis, the pooled prevalence of MetS was found as 37.17% among postmenopausal women (13) . MetS was also found to be more prevalent in postmenopausal women compared with premenopausal women (13) .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis, the pooled prevalence of MetS was found as 37.17% among postmenopausal women (13) . MetS was also found to be more prevalent in postmenopausal women compared with premenopausal women (13) . Additionally, in another meta-analysis, it was also suggested that almost all MetS-associated components except high-density lipoprotein cholesterol (HDL-C) were unfavorably changed after menopause (14) .…”
Section: Introductionmentioning
confidence: 99%